2011
DOI: 10.1103/physrevstab.14.071303
|View full text |Cite|
|
Sign up to set email alerts
|

Polarized beam conditioning in plasma based acceleration

Abstract: The acceleration of polarized electron beams in the blowout regime of plasma-based acceleration is explored. An analytical model for the spin precession of single beam electrons, and depolarization rates of zero emittance electron beams, is derived. The role of finite emittance is examined numerically by solving the equations for the spin precession with a spin tracking algorithm. The analytical model is in very good agreement with the results from 3D particle-in-cell simulations in the limits of validity of o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…electron depolarization during LWFA. As shown below, spin depolarization mainly happens in the injection phase, which is in line with previous studies [29]. Recently, a method is proposed to mitigate this issue by fine tuning the focal position of the Gaussian laser beam to weaken the electron injection [30].…”
Section: Introductionsupporting
confidence: 81%
“…electron depolarization during LWFA. As shown below, spin depolarization mainly happens in the injection phase, which is in line with previous studies [29]. Recently, a method is proposed to mitigate this issue by fine tuning the focal position of the Gaussian laser beam to weaken the electron injection [30].…”
Section: Introductionsupporting
confidence: 81%
“…Such field distributions are also seen in our simulations ( Fig.1 (a)). As already stated in previous works [27][28][29]45], the spin is preserved during steady acceleration but precesses dramatically during the injection phase. That is why we focus on the spin dynamics during injection, where typically one has γ<<1/a e [42,46] and the second term of Eq.…”
Section: Resultssupporting
confidence: 67%
“…It is also found that a polarized electron beam can be produced from nonlinear Compton scattering with an elliptically polarized laser 6 . Along with the rapid development of ultrashort ultraintense laser technology and laser plasma wakefield acceleration scheme, tabletop compact spin polarized electron accelerators may be reality in the near future 7,8 .…”
Section: Introductionmentioning
confidence: 99%